THE INFLUENCE OF FINANCIAL LITERACY AND INCOME ON STUDENTS' FINANCIAL MANAGEMENT BEHAVIOR THROUGH LIFESTYLE AS AN INTERVENING VARIABLE - Octavia, Anita; M anwar, Suhardi; Pajarianto, Hadi (Universitas Islam Lamongan, 2025)
The purpose of this study was to determine the effect of financial literacy and income on the financial management behavior of students through lifestyle as an intervening variable in the 2021 intake, aged 21-25 years at the Muhammadiyah University of Palopo. The sample size used was 80 respondents using the Probability Sampling technique with the random sampling method. Data collection was carried out by distributing questionnaires via Google forms. The analysis technique used was PLS (Partial Least Square) analysis through the Smart PLS 4 program. The results of the study showed (1) Financial literacy has a significant positive effect on lifestyle, (2) Financial literacy has a significant positive effect on financial management behavior, (3) Income has a significant positive effect on lifestyle, (4) Income has a significant positive effect on financial management behavior, (5) Lifestyle does not have a significant effect on financial management behavior, (6) Financial literacy does not have a significant effect on financial management behavior through lifestyle, (7) Income does not have a significant effect on financial management behavior through lifestyle